2008
DOI: 10.1185/030079908x273426
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3, randomized, double-blind study of plasma-derived human thrombin versus bovine thrombin in achieving hemostasis in patients undergoing surgery

Abstract: Plasma-derived human thrombin and bovine thrombin were equivalent in achieving hemostasis within 10, 6, and 3 min and had comparable safety profiles. None of the patients receiving human thrombin developed seroconversion for antibodies to any of the human antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 12 publications
0
71
0
Order By: Relevance
“…For example Surgicel® (Johnson & Johnson, Somerville, N.J., USA) consists of oxidized regenerated cellulose. Topical thrombin [79,80,81] and fibrin [81,82,83] sealants have evidence to show their efficacy in aiding hemostasis and as such can be thought of as adjuncts in an adhesion reduction strategy.…”
Section: Methods Of Adhesion Reductionmentioning
confidence: 99%
“…For example Surgicel® (Johnson & Johnson, Somerville, N.J., USA) consists of oxidized regenerated cellulose. Topical thrombin [79,80,81] and fibrin [81,82,83] sealants have evidence to show their efficacy in aiding hemostasis and as such can be thought of as adjuncts in an adhesion reduction strategy.…”
Section: Methods Of Adhesion Reductionmentioning
confidence: 99%
“…9,10 The members of the panel noted that these trials were powered to demonstrate noninferiority in efficacy parameters and not to demonstrate differences in safety.…”
Section: Clinical Trial Evidencementioning
confidence: 99%
“…A Phase III, randomized, doubleblind multi-center trial reported that plasma-derived human thrombin was just as effective in achieving hemostasis as thrombin derived from a bovine source and had similar safety profiles. Furthermore, none of the patients in the plasma-derived human thrombin group developed seroconversion for antibodies to any of the human antigens [12] . Based on the safety and efficacy data available to date, bovinederived thrombin was shown to be equally effective as either human-derived thrombin or recombinant thrombin [12,20] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, none of the patients in the plasma-derived human thrombin group developed seroconversion for antibodies to any of the human antigens [12] . Based on the safety and efficacy data available to date, bovinederived thrombin was shown to be equally effective as either human-derived thrombin or recombinant thrombin [12,20] . In theory, human-derived thrombin may be a safer agent to be used for topical hemostasis; however, no conclusive evidence exists regarding whether safety profiles of bovinethrombin are better or worse when compared to the usage of human thrombin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation